Consumer Redressal Agencies: How Effective? Kerala Experience - Lizzy E A (Economic and Political Weekly August 7-14, 1993, 1993)
Several agencies have been created under the Consumer Protection Act, 1986. However, if the Kerala experience is anything to go by, the functioning of these agencies is constrained by a variety of factors